Defining and selecting key competencies - Rychen, Dominique Simone [Herausgeber]; Salganik, Laura Hersh [Herausgeber] (Hogrefe and Huber, 2001)
"What skills and competencies are needed in today’s workplaces and other social environments, and how can they best be studied and promoted? The answers to these and other related questions lie in a variety of disciplines, and a multidisciplinary study under the auspices of the OECD (Organization for Economic Cooperation & Development), carried out by the Swiss Federal Statistical Office and the Education Statistics Services of the American Institutes of Research, has now provided a theoretical and conceptual basis for the mass of empirical findings that are currently being generated. This volume brings together contributions from world-renowned authorities, providing a comprehensive overview of current advances and conceptions of life skills and key competencies from a variety of perspectives: historical, philosophical, psychological, sociological, economic, anthropological. Other chapters synthesize these views, looking at common ground with regard to functioning in groups, epistemology, and policy and practice in the real world. The final chapter presents a coherent framework which can be used in further work." (Verlag, BIBB-Doku)
Keywords: L 6.2.1 Standards/Gütekriterien; S 2.2.5 Standards in der beruflichen Bildung; Kompetenz; Kompetenzbegriff; Kompetenzstandards; Kompetenzfeststellung; Schlüsselqualifikation